2017
DOI: 10.1016/j.ejmech.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and anticancer properties of IsoCombretaQuinolines as potent tubulin assembly inhibitors

Abstract: The synthesis and evaluation of a new series of IsoCombretaQuinolines (IsoCoQuines) 2 with a 2-substituted-quinoline in place of the 3,4,5-trimethoxyphenyl ring present in isoCA-4 and CA-4 are described. Most of these compounds displayed a potent cytotoxic activity (IC < 10 nM) against a panel of five human cancer cell lines and inhibited tubulin assembly at a micromolar level. The most potent analogue 2b, having a 3-hydroxy-4-methoxyphenyl as B-ring, led to cell cycle arrest in G2/M phase. Docking studies ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 41 publications
(37 reference statements)
8
45
0
Order By: Relevance
“…Accordingly, the same quinoline‐like system occurred in some of the previously reported 31 compounds . Incidentally, quinoline derivatives were also reported by Shobeiri and Khelifi as potential CBSIs based on experimental evidences. Only 1,2,4‐triazole derivative 16 belongs to the group IV .…”
Section: Resultssupporting
confidence: 85%
“…Accordingly, the same quinoline‐like system occurred in some of the previously reported 31 compounds . Incidentally, quinoline derivatives were also reported by Shobeiri and Khelifi as potential CBSIs based on experimental evidences. Only 1,2,4‐triazole derivative 16 belongs to the group IV .…”
Section: Resultssupporting
confidence: 85%
“…

Novel quinoline derivatives carrying nitrones and oxime as nitric oxide donors were prepared and characterized using different spectroscopic techniques. Several mechanisms can explain the anticancer effect of quinoline derivatives including: topoisomerase inhibition, [21][22][23] DNA intercalation, [24] protein kinases inhibition, [25][26][27] tubulin polymerase inhibition, [28][29][30][31] and induction of apoptosis. Antiproliferative screening results showed that the 2-benzylthioquinoline nitrones 6e and 6f and the 2-methylthio analogues 6g and 6h exhibited promising antiproliferative activity especially against leukemia and colon cancer cell lines.

…”
mentioning
confidence: 99%
“…Antiproliferative screening results showed that the 2-benzylthioquinoline nitrones 6e and 6f and the 2-methylthio analogues 6g and 6h exhibited promising antiproliferative activity especially against leukemia and colon cancer cell lines. [31] Compound II exhibits remarkable anticancer activity against HL60 cancer cell line with IC 50 of 0.68 μM (Figure 1). A remarkable overexpression of caspase-3 protein levels was observed in cells treated with the tested compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the quinoline moiety is based on work by Khelifi et al in which a quinoline structure was predicted by docking studies to form a hydrogen bond with Cys-241 residue of the CBS through the N-1 atom of the quinoline ring. Quinoline 48 (Figure 7) displayed nano-and sub-nanomolar levels of cytotoxicity against five cancer cell lines and inhibited tubulin polymerization with micromolar IC 50 values [105].…”
Section: Quinoline and Indole Derivatives Of Isoca-4mentioning
confidence: 99%